(untitled) (West African Journal on Sustainable Development, 2024)
Background Intimate partner violence in pregnancy is a hidden global pandemic, an increasing social injustice to women especially in developing countries. It interferes with the Sustainable Development Goals (SDG) 3 and 5, hindering the achievement of good health and well-being for all; and stagnates attaining gender equity and equality. Aim This study investigated the prevalence and factors contributing to intimate partner violence in pregnancy among antenatal attendees in a tertiary health facility in Anambra state. Methods The study was a facility-based descriptive cross-sectional study with in-depth interviews (IDI) conducted among 400 respondents at the Ante-Natal clinics of Nnamdi Azikiwe University Teaching Hospital. Twenty of the victims were purposively selected for in-depth interviews. Results In the study, 61% of the respondents were aged 25 to 34 years and the mean age of respondents was 30.0 years (SD ±5.3). The overall prevalence of intimate partner violence (IPV) in pregnancy was 27.3%. The prevalence of psychological, controlling behaviours, physical and sexual IPV were 17.0%, 16.0%, 5.3%, and 1.0% respectively. The factors significantly associated with IPV in pregnancy were the educational status of the partner, experiencing IPV before pregnancy, witnessed IPV during childhood or adolescence, and justifying husband to beat spouse if she offends him. In the in-depth interview, All the participants had experienced controlling behaviours especially the ’monitoring your movements’. Poverty and poor business sales were factors associated with IPV in pregnancy. Conclusion The increasing economic hardship may worsen IPV. Creating awareness, screening of pregnant women for IPV, the political will and appropriate interventions will help in reducing the menace of IPV in pregnancy.